EFFECT OF THE ADDITION OF GINGER AND PANDAN EXTRACT ON SOY MILK PROCESSED - Hilda Meisya Arif; Eska Prima Monique Damarsiwi (SINTA Journal (Science, Technology, and Agricultural), 2021)
Soy milk is a processed product derived from soy bean extraction. Protein contained in soy milk has almost the same amino acid content as animal milk so it can be used as a substitute milk for those who are allergic to animal milk. This soy milk processing does not need to use equipment that is complicated enough, just a simple tool and without special skills. Ginger (Zingiber officinale Roscoe) is one of the findings that belong to the living pharmacy plant, which is believed to eliminate colds, prevent or reduce influenza, cough rheumatism and as an analgesic and anti-inflammatory medicine. Pandan (Pandanaceae) is a monocot plant that has a distinctive aroma.  Pandan also has a green color that can be used as a dye to add to the appeal of soy milk.  Fragrance in pandans can be used for sedatives and at certain levels useful in shortening sleep induction. Testing used 30 panelists with the RAL method and organoleptic testing of color, taste and aroma. The results showed that the PH in soy milk at the treatment of P1,P2,P3 experienced a significant increase so it can be said that the pH of soy milk with the addition of extrax percentage of ginger and pandan by (2%.5% and 7%) increased. Increased PH in soy milk results in the taste of soy milk increasingly bitter and bitter. In organoleptic testing the color of the P2 treatment was preferred by panelists with a value of 4.78. Organoleptic taste obtained the results of P1 has a value of 3.5 which means panelists prefer the taste of soy milk with a treatment of 2% extrax ginger and pandan. Sendagkan on organoleptic testing aroma panelists prefer P3 treatment with a value of 3.76.